A LEVITE AND HIS CONCUBINE ‘Seorang Lewi dan Gundiknya’ Sebuah Analisis PAK dan Implikasinya terhadap Keluarga - Tulangouw , Maria Elisa (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
This article starts with looking at the text in the bible related to a Levite and his concubine. There are some critical about the tragedy of raped the concubine, who was impact the war to Benyamin descendant, but also to make us realize about how great the relation among the member of family, especially the son in law with his father in law. I’m writing this article in the purpose for open our new paradigm about how we must facing & survive to the reality when living together as household. I’m using literature books and method in qualitative approach to founding the meaning. As part of an analyst the Christian Education in relation between husband and wife, because has great impact to the whole member of family. This story also talking about a Levi who love his wife very much through his real action, so the result of this article to finding the values of Christian Family for inherited.